(untitled) (Research, Society and Development, 2022)
Objective: To survey data on the sociodemographic and health care profile of women who had children with CS in the Baixada Maranhense and to identify the cities with the highest concentration of cases in this region. Method: Retrospective, descriptive, quantitative study that characterized the sociodemographic and health care aspects related to women with children with Congenital Syphilis, through 48 notification forms of Congenital Syphilis made available by the Regional Health Department and 76 cases reported in the National System of Notifiable Diseases in the period from 2010 to 2020. The ArcGIS software was used for georeferencing. Results: 48% of women are in the young adult age group (20 to 24 years), 67% were brown, 33% had incomplete elementary school education and 40% were farmers. 77% had prenatal care, however, 38% were diagnosed with syphilis only postpartum. 52.08% of the partners did not undergo treatment. Conclusion: There is a deficiency regarding the prenatal care provided to women. It is essential that there is the establishment of strategies that seek to reduce the incidence of Congenital Syphilis cases.